A method for preparing corrosion-resistant DLC film layer on inner wall of pipeline

Through high-pressure pulse technology and multi-step plasma enhanced chemical vapor deposition process, the problems of poor binding force and insufficient corrosion resistance of DLC film layers are solved, and a dense film layer is prepared, which significantly improves the corrosion resistance and service life of the pipeline.

CN115110056BActive Publication Date: 2024-12-27SONGSHAN LAKE MATERIALS LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210570733.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-24
Publication Date
2024-12-27
Estimated Expiration
2042-05-24

AI Technical Summary

Technical Problem

The existing DLC ​​film layer has problems such as poor bonding force, looseness and high stress in the field of pipeline inner wall coating, resulting in insufficient corrosion resistance.

Method used

Using high-voltage pulse technology, by adjusting the pulse voltage, frequency and pulse width, the plasma density and energy are improved, the bonding force between the membrane layer and the substrate is enhanced, and the chemical vapor deposition process is enhanced through multi-step plasma, the membrane layer is compacted, and the membrane layer is adjusted. Structure and stress improve the density and corrosion resistance of the film layer.

Benefits of technology

A dense DLC film layer was prepared to meet the requirements of 96h neutral salt spray corrosion, without corrosion, significantly improving the corrosion resistance of the pipeline and extending the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115110056B_ABST
    Figure CN115110056B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a corrosion-resistant DLC film layer on the inner wall of a pipeline, and belongs to the field of thin film technology. It comprises the following steps: 1. cleaning before plating; 2. vacuuming the pipeline installation; 3. plasma cleaning; 4. base layer deposition; 5. Si-doped DLC layer deposition; 6. DCL deposition; 7. The sixth step and the fifth step are performed alternately, with an interval of 10 minutes and a total time of 120 minutes. By using the pipeline as a cathode and the vacuum chambers at both ends as anodes, plasma enhanced chemical vapor deposition is performed on the inner wall of the pipeline to form a corrosion-resistant film layer of Si base layer-Si-DLC layer-DCL layer. The method is simple to operate and easy to control. The film performance can be controlled by changing the deposition parameters, and the obtained film has the advantages of dense film layer and good salt corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thin films, and in particular to a method for preparing a corrosion-resistant DLC film layer on an inner wall of a pipeline. Background Art

[0002] In actual production and life, pipelines are used more and more widely. For example, in the oil industry, oil and natural gas are mostly transported by pipelines; in chemical production, a large number of chemical reagents are also transported by pipelines; our daily drinking water is also transported by pipelines. Pipelines play an important role whether as workpieces or transportation tools. However, pipelines are easily corroded by the transported substances during use, which makes the pipelines easily damaged and causes economic losses. For these reasons, it is very necessary to design a corrosion-resistant film layer deposited on the inner wall of the pipeline.

[0003] At present, diamond-like carbon film (DLC) is usually used as a coating to protect the surface of materials due to its high hardness, stable chemical properties, low friction coefficient and other properties. Factors that affect the corrosion resistance of the DLC film include loose film with pinholes, large residual stress in the film, and poor film-base bonding. At present, the hollow cathode method is mainly used to prepare the DLC film in the field of pipeline inner wall coating. Some researchers use doping with other elements to improve the performance of the film, but the doping of elements may cause the film to be loose and not dense or the elements to dissolve. Therefore, it is necessary to design a process to prepare a film with a dense film layer and good film-base bonding to achieve protection of the inner wall of the pipeline. Summary of the invention

[0004] In view of the defects of poor interlayer bonding and corrosion resistance of DLC films in the prior art, the present invention provides a method for preparing a corrosion-resistant DLC film layer on the inner wall of a pipeline. The hollow pipeline is used as a cathode for film coating by using high-voltage pulse technology, and the density of plasma is increased by means of high-voltage pulses. The high voltage increases the energy of ions to strengthen the cleaning and bombardment of the substrate, improves the bonding force between the film layer and the substrate, and compacts the film layer to improve the density of the film layer. Then, by adjusting the pulse parameters, the stress of the film layer is relieved, the thickness of the film layer is increased, and the corrosion resistance of the film layer is improved.

[0005] The present invention provides a method for preparing a corrosion-resistant DLC film layer on the inner wall of a pipeline, comprising the following steps:

[0006] S1. After sandblasting, the inner surface of the pipeline is ultrasonically cleaned and dried;

[0007] S2. After the pipeline is installed, vacuum is drawn to a vacuum degree of 1.0×10 -5 ~1.0×10 -3 Pa;

[0008] S3, passing Ar into the interior of the pipeline for plasma enhanced chemical vapor deposition (PECVD), with a gas pressure of 2-20 Pa, the pipeline as the cathode, a pulse voltage of 5000-10000 V, a frequency of 100-3000 Hz, a pulse width of 5-1000 us, and a time of 30-200 min;

[0009] S4, introducing Ar and tetramethylsilane into the pipeline at the same time for plasma enhanced chemical vapor deposition, with a gas pressure of 3-15 Pa, the pipeline as the cathode, a pulse voltage of 5000-10000 V, a frequency of 100-3000 Hz, a pulse width of 10-1000 us, and a time of 30-100 min;

[0010] S5. Ar, tetramethylsilane and acetylene are introduced into the pipeline at the same time for plasma enhanced chemical vapor deposition, with a gas pressure of 5-20 Pa, the pipeline as the cathode, a pulse voltage of 3000-10000 V, a frequency of 100-3000 Hz, a pulse width of 10-1000 us, and a time of 10-60 min;

[0011] S6. Ar and acetylene are introduced into the pipeline at the same time for plasma enhanced chemical vapor deposition, with a gas pressure of 5-20 Pa, the pipeline as the cathode, a pulse voltage of 3000-10000 V, a frequency of 100-3000 Hz, a pulse width of 10-1000 us, and a time of 10-300 min;

[0012] S7. Repeat steps S5 and S6 with an interval of min.

[0013] Preferably, in step S3, the Ar flow rate is 50-500 sccm.

[0014] Preferably, in step S4, the Ar flow rate is 100-500 sccm, and the tetramethylsilane flow rate is 10-100 sccm.

[0015] Preferably, in step S5, the flow rate of Ar is 100-500 sccm, the flow rate of tetramethylsilane is 10-100 sccm, and the flow rate of acetylene is 50-300 sccm.

[0016] Preferably, in step S6, the Ar flow rate is 100-500 sccm, and the acetylene flow rate is 50-300 sccm.

[0017] Preferably, in step S7, the number of repetitions is ≥ 1. The number of modulations is adjusted according to actual conditions.

[0018] The present invention adopts high-voltage pulse technology, takes a pipeline as a cathode, and performs PECVD on the inner wall of the pipeline to prepare a DLC coating. The plasma density in the pipeline is regulated by adjusting the pulse voltage, frequency and pulse width, and then the microstructure of the film layer is regulated to improve the compactness and bonding strength. In the cleaning and priming stages, the high pulse voltage and frequency pulse width increase the ionization of the gas, increase the plasma density and energy, enhance the cleaning bombardment activation of the substrate surface, and inject a part of the atoms into the substrate surface, thereby improving the bonding strength between the film layer and the substrate; in the deposition of Si-DLC and DLC layer stages, by increasing the pulse voltage, adjusting the frequency and pulse width, the ionization of TMS and acetylene is enhanced, the plasma density is increased, and the deposition rate and compactness of the film layer are improved; thereafter, the pulse voltage is reduced, the frequency and pulse width are adjusted, the plasma density and energy are regulated, and then the deposition rate, the film layer structure and compactness of the film layer are adjusted, and the ion bombardment energy is reduced, and the internal stress of the film layer is also reduced. By regularly adjusting the pulse voltage, frequency and pulse width, the film structure and stress can be regulated to prepare a thicker film layer. Finally, the pulse parameters are adjusted to deposit a dense pure DLC film layer to further improve the corrosion resistance of the film layer.

[0019] The technical solution of the present invention has the following advantages:

[0020] The present invention provides a method for preparing a corrosion-resistant DLC film layer on the inner wall of a pipeline. The structure, density and internal stress of the film layer can be adjusted by adjusting different pulse voltages, frequencies and pulse widths and controlling the pipeline plasma density. Film layers with different performances can be prepared according to different requirements.

[0021] The preparation method provided by the present invention is simple and convenient to operate, and a corrosion-resistant DLC film layer can be prepared on the inner wall of a pipeline with different aspect ratios and made of different materials by adjusting different pulse parameters.

[0022] The DLC film prepared by the preparation method provided by the present invention has a dense film layer, meets the 96h neutral salt spray corrosion requirement, and has no corrosion, thereby improving the corrosion resistance of the pipeline, extending the service life of the pipeline, and increasing the economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a cross-sectional SEM image of the DLC film layer prepared in Example 1.

[0024] Figure 2 This is the indentation test result of the DLC film layer prepared in Example 1.

[0025] Figure 3 A schematic diagram of the neutral salt spray corrosion results of the DLC film prepared in Example 1;

[0026] Among them, a, 24h, b, 36h, c, 48h, d, 96h. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described below in conjunction with embodiments, comparative examples and accompanying drawings.

[0028] Example 1

[0029] 1. Cleaning before plating

[0030] The inner surface of the pipe is sandblasted, ultrasonically cleaned, and dried;

[0031] 2. Vacuuming the pipeline installation

[0032] The pipeline is installed on the inner wall coating equipment and vacuumed to a vacuum degree of 1.0×10 -5 Pa;

[0033] 3. Plasma cleaning

[0034] Ar gas was sent into the pipeline through the gas guide tube, with an Ar flow rate of 500 sccm, a gas pressure of 8 Pa, a pulse voltage of 8000 V, a frequency of 500 Hz, a pulse width of 30 us, and a time of 100 min;

[0035] 4. Base Deposition

[0036] Ar and tetramethylsilane (TMS) were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 30 sccm, a gas pressure of 10 Pa, a pulse voltage of 10000 V, a frequency of 1000 Hz, a pulse width of 100 us, and a time of 50 min;

[0037] 5. Deposition of Si-doped DLC layer

[0038] Ar, tetramethylsilane (TMS), and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 50 sccm, an acetylene flow rate of 400 sccm, a gas pressure of 20 Pa, a pulse voltage of 8000 V, a frequency of 3000 Hz, a pulse width of 100 us, and a time of 30 min;

[0039] 6. DCL deposition

[0040] Ar and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, an acetylene flow rate of 300 sccm, a gas pressure of 15 Pa, a pulse voltage of 10000 V, a frequency of 800 Hz, a pulse width of 50 us, and a time of 30 min;

[0041] 7. The sixth step and the fifth step are performed alternately, with an interval of 10 minutes and a total time of 120 minutes. The various properties of the obtained diamond-like composite film are tested; the density and defects of the film cross section are observed by scanning electron microscopy, and the film thickness is measured; the corrosion resistance of the film is tested by neutral salt spray corrosion; and the bonding strength of the film is tested by indentation. The test results are shown in Table 1.

[0042] Example 2

[0043] 1. Cleaning before plating

[0044] The inner surface of the pipe is sandblasted, ultrasonically cleaned, and dried;

[0045] 2. Vacuuming the pipeline installation

[0046] The pipeline is installed on the inner wall coating equipment and vacuumed to a vacuum degree of 1.0×10 -5 Pa;

[0047] 3. Plasma cleaning

[0048] Ar gas was sent into the pipeline through the gas guide tube, with an Ar flow rate of 600 sccm, a gas pressure of 10 Pa, a pulse voltage of 8000 V, a frequency of 500 Hz, a pulse width of 100 us, and a time of 100 min;

[0049] 4. Base Deposition

[0050] Ar and tetramethylsilane (TMS) were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 30 sccm, a gas pressure of 10 Pa, a pulse voltage of 10000 V, a frequency of 1000 Hz, a pulse width of 100 us, and a time of 50 min;

[0051] 5. Deposition of Si-doped DLC layer

[0052] Ar, tetramethylsilane (TMS), and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 50 sccm, an acetylene flow rate of 400 sccm, a gas pressure of 20 Pa, a pulse voltage of 8000 V, a frequency of 3000 Hz, a pulse width of 100 us, and a time of 30 min;

[0053] 6. DCL deposition

[0054] Ar and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, an acetylene flow rate of 300 sccm, a gas pressure of 15 Pa, a pulse voltage of 10000 V, a frequency of 800 Hz, a pulse width of 50 us, and a time of 30 min;

[0055] 7. Step 6 and step 5 are performed alternately, with an interval of 20 minutes and a total time of 120 minutes.

[0056] The various properties of the obtained diamond-like composite film were tested according to the testing method of Example 1. The test results are shown in Table 1.

[0057] Example 3

[0058] 1. Cleaning before plating

[0059] The inner surface of the pipe is sandblasted, ultrasonically cleaned, and dried;

[0060] 2. Vacuuming the pipeline installation

[0061] The pipeline is installed on the inner wall coating equipment and vacuumed to a vacuum degree of 1.0×10 -5 Pa;

[0062] 3. Plasma cleaning

[0063] Ar gas was sent into the pipeline through the gas guide tube, with an Ar flow rate of 500 sccm, a gas pressure of 10 Pa, a pulse voltage of 10000 V, a frequency of 1000 Hz, a pulse width of 100 us, and a time of 200 min;

[0064] 4. Base Deposition

[0065] Ar and tetramethylsilane (TMS) were introduced into the pipeline at the same time, with an Ar flow rate of 300 sccm, a TMS flow rate of 100 sccm, a gas pressure of 10 Pa, a pulse voltage of 9000 V, a frequency of 3000 Hz, a pulse width of 80 us, and a time of 10 min;

[0066] 5. Deposition of Si-doped DLC layer

[0067] Ar, tetramethylsilane (TMS), and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 50 sccm, an acetylene flow rate of 400 sccm, a gas pressure of 20 Pa, a pulse voltage of 8000 V, a frequency of 3000 Hz, a pulse width of 100 us, and a time of 30 min;

[0068] 6. DCL deposition

[0069] Ar and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, an acetylene flow rate of 300 sccm, a gas pressure of 15 Pa, a pulse voltage of 10000 V, a frequency of 800 Hz, a pulse width of 50 us, and a time of 30 min;

[0070] 7. Step 6 and step 5 are performed alternately, with an interval of 20 minutes and a total time of 120 minutes.

[0071] The various properties of the obtained diamond-like composite film were tested according to the testing method of Example 1. The test results are shown in Table 1.

[0072] Example 4

[0073] 1. Cleaning before plating

[0074] The inner surface of the pipe is sandblasted, ultrasonically cleaned, and dried;

[0075] 2. Vacuuming the pipeline installation

[0076] The pipeline is installed on the inner wall coating equipment and vacuumed to a vacuum degree of 1.0×10 -5 Pa;

[0077] 3. Plasma cleaning

[0078] Ar gas was sent into the pipeline through the gas guide tube, with an Ar flow rate of 500 sccm, a gas pressure of 10 Pa, a pulse voltage of 10000 V, a frequency of 1000 Hz, a pulse width of 100 us, and a time of 200 min;

[0079] 4. Base Deposition

[0080] Ar and tetramethylsilane (TMS) were introduced into the pipeline at the same time, with an Ar flow rate of 300 sccm, a TMS flow rate of 100 sccm, a gas pressure of 10 Pa, a pulse voltage of 9000 V, a frequency of 300 Hz, a pulse width of 80 us, and a time of 10 min;

[0081] 5. Deposition of Si-doped DLC layer

[0082] Ar, tetramethylsilane (TMS), and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 50 sccm, an acetylene flow rate of 400 sccm, a gas pressure of 20 Pa, a pulse voltage of 10000 V, a frequency of 3000 Hz, a pulse width of 100 us, and a time of 30 min;

[0083] 6. DCL deposition

[0084] Ar and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 100 sccm, an acetylene flow rate of 300 sccm, a gas pressure of 15 Pa, a pulse voltage of 8000 V, a frequency of 600 Hz, a pulse width of 100 us, and a time of 60 min;

[0085] 7. Step 6 and step 5 are performed alternately, with an interval of 30 minutes and a total time of 120 minutes.

[0086] The various properties of the obtained diamond-like composite film were tested according to the testing method of Example 1. The test results are shown in Table 1.

[0087] Comparative Example 1

[0088] 1. Cleaning before plating

[0089] The inner surface of the pipe is sandblasted, ultrasonically cleaned, and dried;

[0090] 2. Vacuuming the pipeline installation

[0091] The pipeline is installed on the inner wall coating equipment and vacuumed to a vacuum degree of 1.0×10 -5 Pa;

[0092] 3. Plasma cleaning

[0093] Ar gas was sent into the pipeline through the gas guide tube, with an Ar flow rate of 500 sccm, a gas pressure of 8 Pa, a pulse voltage of 8000 V, a frequency of 500 Hz, a pulse width of 30 us, and a time of 20 min;

[0094] 4. Base Deposition

[0095] Ar and tetramethylsilane (TMS) were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 30 sccm, a gas pressure of 10 Pa, a pulse voltage of 3000 V, a frequency of 100 Hz, a pulse width of 10 us, and a time of 10 min;

[0096] 5. Si-DLC layer deposition

[0097] Ar, tetramethylsilane (TMS), and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 50 sccm, an acetylene flow rate of 400 sccm, a gas pressure of 20 Pa, a pulse voltage of 8000 V, a frequency of 3000 Hz, a pulse width of 100 us, and a time of 30 min;

[0098] 6. DCL deposition

[0099] Ar and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, an acetylene flow rate of 300 sccm, a gas pressure of 15 Pa, a pulse voltage of 10000 V, a frequency of 800 Hz, a pulse width of 50 us, and a time of 30 min;

[0100] 7. Step 6 and step 5 are performed alternately, with an interval of 10 minutes and a total time of 120 minutes.

[0101] Comparative Example 2

[0102] 1. Cleaning before plating

[0103] The inner surface of the pipe is sandblasted, ultrasonically cleaned, and dried;

[0104] 2. Vacuuming the pipeline installation

[0105] The pipeline is installed on the inner wall coating equipment and vacuumed to a vacuum degree of 1.0×10 -5Pa;

[0106] 3. Plasma cleaning

[0107] Ar gas was sent into the pipeline through the gas guide tube, with an Ar flow rate of 600 sccm, a gas pressure of 10 Pa, a pulse voltage of 8000 V, a frequency of 500 Hz, a pulse width of 100 us, and a time of 100 min;

[0108] 4. Base Deposition

[0109] Ar and tetramethylsilane (TMS) were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 30 sccm, a gas pressure of 10 Pa, a pulse voltage of 10000 V, a frequency of 1000 Hz, a pulse width of 100 us, and a time of 50 min;

[0110] 5. Deposition of Si-doped DLC layer

[0111] Ar, tetramethylsilane (TMS), and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 50 sccm, an acetylene flow rate of 400 sccm, a gas pressure of 20 Pa, a pulse voltage of 10000 V, a frequency of 3000 Hz, a pulse width of 100 us, and a time of 30 min;

[0112] 6. DCL deposition

[0113] Ar and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, an acetylene flow rate of 300 sccm, a gas pressure of 15 Pa, a pulse voltage of 10000 V, a frequency of 3000 Hz, a pulse width of 100 us, and a time of 30 min;

[0114] 7. Step 6 and step 5 are performed alternately, with an interval of 20 minutes and a total time of 120 minutes.

[0115] The various properties of the obtained diamond-like composite film were tested according to the testing method of Example 1. The test results are shown in Table 1.

[0116] Comparative Example 3

[0117] 1. Cleaning before plating

[0118] The inner surface of the pipe is sandblasted, ultrasonically cleaned, and dried;

[0119] 2. Vacuuming the pipeline installation

[0120] The pipeline is installed on the inner wall coating equipment and vacuumed to a vacuum degree of 1.0×10 -5 Pa;

[0121] 3. Plasma cleaning

[0122] Ar gas was sent into the pipeline through the gas guide tube, with an Ar flow rate of 500 sccm, a gas pressure of 10 Pa, a pulse voltage of 10000 V, a frequency of 1000 Hz, a pulse width of 100 us, and a time of 200 min;

[0123] 4. Base Deposition

[0124] Ar and tetramethylsilane (TMS) were introduced into the pipeline at the same time, with an Ar flow rate of 300 sccm, a TMS flow rate of 100 sccm, a gas pressure of 10 Pa, a pulse voltage of 9000 V, a frequency of 3000 Hz, a pulse width of 80 us, and a time of 10 min;

[0125] 5. Deposition of Si-doped DLC layer

[0126] Ar, tetramethylsilane (TMS), and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 50 sccm, an acetylene flow rate of 400 sccm, a gas pressure of 20 Pa, a pulse voltage of 1000 V, a frequency of 100 Hz, a pulse width of 10 us, and a time of 30 min;

[0127] 6. DCL deposition

[0128] Ar and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, an acetylene flow rate of 300 sccm, a gas pressure of 15 Pa, a pulse voltage of 1000 V, a frequency of 100 Hz, a pulse width of 10 us, and a time of 30 min;

[0129] 7. Step 6 and step 5 are performed alternately, with an interval of 20 minutes and a total time of 120 minutes.

[0130] The various properties of the obtained diamond-like composite film were tested according to the testing method of Example 1. The test results are shown in Table 1.

[0131] Comparative Example 4

[0132] 1. Cleaning before plating

[0133] The inner surface of the pipe is sandblasted, ultrasonically cleaned, and dried;

[0134] 2. Vacuuming the pipeline installation

[0135] The pipeline is installed on the inner wall coating equipment and vacuumed to a vacuum degree of 1.0×10 -5 Pa;

[0136] 3. Plasma cleaning

[0137] Ar gas was sent into the pipeline through the gas guide tube, with an Ar flow rate of 500 sccm, a gas pressure of 10 Pa, a pulse voltage of 10000 V, a frequency of 1000 Hz, a pulse width of 100 us, and a time of 200 min;

[0138] 4. Base Deposition

[0139] Ar and tetramethylsilane (TMS) were introduced into the pipeline at the same time, with an Ar flow rate of 300 sccm, a TMS flow rate of 100 sccm, a gas pressure of 10 Pa, a pulse voltage of 9000 V, a frequency of 300 Hz, a pulse width of 80 us, and a time of 10 min;

[0140] 5. Deposition of Si-doped DLC layer

[0141] Ar, tetramethylsilane (TMS), and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 500 sccm, a TMS flow rate of 50 sccm, an acetylene flow rate of 400 sccm, a gas pressure of 20 Pa, a pulse voltage of 3000 V, a frequency of 300 Hz, a pulse width of 20 us, and a time of 10 min;

[0142] 6. DCL deposition

[0143] Ar and acetylene were introduced into the pipeline at the same time, with an Ar flow rate of 100 sccm, an acetylene flow rate of 300 sccm, a gas pressure of 15 Pa, a pulse voltage of 4000 V, a frequency of 200 Hz, a pulse width of 20 us, and a time of 10 min;

[0144] 7. Step 6 and step 5 are performed alternately, with an interval of 30 minutes and a total time of 120 minutes.

[0145] The various properties of the obtained diamond-like composite film were tested according to the testing method of Example 1. The test results are shown in Table 1.

[0146] As can be seen from Table 1, in Examples 1-3 of the present invention, a DLC film layer was prepared on the inner wall of a pipe using a high-voltage pulse technology, and a scanning electron microscope was used to observe the cross section of the film layer. Figure 1 As shown, the film layer is dense, and no defects such as cracks and pinholes are found. The indentation test is carried out, and the load used by the hardness tester is 1470N, the holding time is 10s, and the diamond indenter is compared with the VDI3198 standard atlas. There is no film collapse at the edge of the indentation, and only a small amount of cracks, such as Figure 2 , indicating that the membrane-base bonding strength and the toughness of the membrane layer are good, and can reach the HF1-HF2 level. The corrosion resistance of the membrane layer is tested by neutral salt spray corrosion according to the national standard GB / T10125. After 96 hours of salt spray corrosion, the sample Figure 3, through naked eye and optical microscope observation, no pitting and corrosion occurred on the surface of the film layer, indicating that the film layer has excellent corrosion resistance. It should be noted that the performance of the DLC film layers prepared in the other examples is equivalent to that of Example 1.

[0147] The performance tests of the DLC film layers prepared by the embodiments and comparative examples are shown in Table 1. Comparative Example 1, cleaning time 20min; the pulse voltage of the base layer is 3000V, the frequency is 100Hz, the pulse width is 10us, and the time is 10min, and the film-base interface bonding force decreases; Comparative Example 2, the pulse voltage is 10000V, the frequency is 3000Hz, the pulse width is 100us, and the time is 30min when preparing the film layer; the stress of the film layer increases, resulting in the collapse of the film layer during the indentation test. Comparative Example 3, the pulse voltage is 1000V, the frequency is 100Hz, the pulse width is 10us, and the time is 30min when preparing the film layer; Comparative Example 4, the pulse voltage is 4000V, the frequency is 200Hz, and the pulse width is 20us when preparing the film layer, the gas ionization decreases, the deposition rate of the film layer decreases, the film layer is loose, and the corrosion resistance decreases.

[0148] Table 1

[0149]

[0150] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a corrosion-resistant DLC film layer on the inner wall of a pipeline, characterized in that: The following steps are involved: S1. After sandblasting, the inner surface of the pipeline is ultrasonically cleaned and dried; S2. After the pipeline is installed, vacuum is evacuated to a vacuum degree of 1.0×10 -5 ~1.0×10 -3 Pa; S3, passing Ar into the pipeline for plasma enhanced chemical vapor deposition, with a gas pressure of 2-20 Pa, the pipeline as the cathode, a pulse voltage of 5000-10000 V, a frequency of 100-3000 Hz, a pulse width of 5-1000 us, and a time of 30-200 min; Increase the ionization of the gas, improve the plasma density and energy, enhance the cleaning bombardment activation of the substrate surface, and inject a part of the atoms into the substrate surface, thereby improving the bonding strength between the film layer and the substrate; S4, introducing Ar and tetramethylsilane into the pipeline at the same time for plasma enhanced chemical vapor deposition, with a gas pressure of 3-15 Pa, the pipeline as the cathode, a pulse voltage of 5000-10000 V, a frequency of 100-3000 Hz, a pulse width of 10-1000 us, and a time of 30-100 min; Increase the pulse voltage, adjust the frequency and pulse width, enhance the ionization of TMS and acetylene, increase the plasma density, and improve the film deposition rate and density; S5. Ar, tetramethylsilane and acetylene are introduced into the pipeline at the same time for plasma enhanced chemical vapor deposition, with a gas pressure of 5-20 Pa, the pipeline as the cathode, a pulse voltage of 3000-10000 V, a frequency of 100-3000 Hz, a pulse width of 10-1000 us, and a time of 10-60 min; S6. Ar and acetylene are introduced into the pipeline at the same time for plasma enhanced chemical vapor deposition, with a gas pressure of 5-20 Pa, the pipeline as the cathode, a pulse voltage of 3000-10000 V, a frequency of 100-3000 Hz, a pulse width of 10-1000 us, and a time of 10-300 min; Reduce the pulse voltage, adjust the frequency and pulse width, control the plasma density and energy, adjust the deposition rate, film structure and density of the film, and reduce the ion bombardment energy and the internal stress of the film; Regularly adjust the pulse voltage, frequency and pulse width to control the film structure and stress, so as to prepare a thicker film layer; S7, repeat step S5 and step S6, with an interval of 1-100 minutes; Finally, the pulse parameters are adjusted to deposit a dense pure DLC film layer to further improve the corrosion resistance of the film layer.

2. The method for preparing a corrosion-resistant DLC film layer on the inner wall of a pipeline according to claim 1, characterized in that: In step S3, the Ar flow rate is 50-500 sccm.

3. The method for preparing a corrosion-resistant DLC film layer on the inner wall of a pipeline according to claim 1, characterized in that: In step S4, the Ar flow rate is 100-500 sccm, and the tetramethylsilane flow rate is 10-100 sccm.

4. The method for preparing a corrosion-resistant DLC film layer on the inner wall of a pipeline according to claim 1, characterized in that: In step S5, the Ar flow rate is 100-500 sccm, the tetramethylsilane flow rate is 10-100 sccm, and the acetylene flow rate is 50-300 sccm.

5. The method for preparing a corrosion-resistant DLC film layer on the inner wall of a pipeline according to claim 1, characterized in that: In step S6, the Ar flow rate is 100-500 sccm, and the acetylene flow rate is 50-300 sccm.

6. The method for preparing a corrosion-resistant DLC film layer on the inner wall of a pipeline according to claim 1, characterized in that: In step S7, the number of repetitions is ≥ 1.